Kajian Tafsir Al-Kashshaf Karya Al-Zamakhshari - Budi Hariyanto (HUMANISTIKA : Jurnal Keislaman, 2016)
The presence of the interpretation of the Qur'an in the midst of Muslims is an intermediary instrument to bring together human inequalitiesin translating Divine messages stored in it. And the existence of al-Kashshaf's interpretation by al-Zamakhshari is one of the tools used to translate the language of the Qur'an to humanity. Tafsir al-Kashshaf is one of the famous tafsir bi al-ra'yi books of mu'tazili, which in its discussion uses language and literary approaches. The method of interpretation is viewed from several aspects; 1) The source of interpretation is the interpretation of bi al-ra'yi. 2) In terms of explanation is an interpretation of muqarin. 3) The broad aspect of interpretation is bi al-itnabi / tafsili. 4) The terms of the target & orderly verse is tahlili.